Serum vitamin D levels and their correlation with pro-inflammatory prostaglandins in Acute myeloid leukemia: a cross-sectional analysis - Hossein Ghasemi Moghaddam; Nasrin Gholami; Ali Esfahani; Zohreh Ghoreish; Amirreza Khalaji (Scientific Reports, 2024)
Abstract Background This study investigated the association between prostaglandins, vitamin D levels, and their potential role in acute myeloid leukemia (AML). Previous research has shown prostaglandins’ stimulatory effects and vitamin D’s inhibitory effects in various malignancies. Methods This cross-sectional study evaluated 54 AML patients at Shahid Ghazi Center of Imam Reza Hospital in Tabriz. Prostaglandin E2 (PGE2), Cyclooxygenase-2 (COX-2), and serum vitamin D levels, as well as gene expression of 5-hydroxyprostaglandin dehydrogenase (15-PGDH), COX-2, PGE2 synthase, and vitamin D receptor (VDR), were measured. Relationships were assessed between vitamin D levels, COX-2 and PGE2 expression, serum levels, and treatment outcomes. Results Median serum vitamin D level was 18.25 ng/mL (range: 4.00-72.70). There was no significant association between serum vitamin D levels and expression or serum levels of COX-2, PGE2 synthase, and 15-PGDH. VDR gene expression and serum levels showed significant direct correlations with PGE2 and COX-2 gene expression and serum concentrations and inverse correlations with 15-PGDH expression (P < 0.05). No statistically significant correlation was observed between vitamin D status, PGE2, COX-2, and 15-PGDH with treatment outcomes. Conclusion This study on AML patients showed no significant correlation between vitamin D levels and COX-2, PGE2 synthase, or 15-PGDH. VDR expression correlated positively with PGE2 and COX-2 but negatively with 15-PGDH. No associations were found between these factors and therapy outcomes.